Usrah as a principle of good governance at the International Islamic University Malaysia - Awang Abdul Muizz Awang Marusin; Mohd. Azri Ibrahim; Suraya Sintang (2018)
This study tries to analyse the ability of the International Islamic University Malaysia (IIUM) to manage Usrah and the possibility of Usrah to be a principle of good governance. As a qualitative study, a case study involving all members of the management of Usrah in IIUM was conducted throughout Academic Year 2016/2017. Findings shown that the management of Usrah was able to practice good governance. This was contributed by the members themselves who understand the principles of good governance, who are skillful in organising internal and external Usrah activities, and who are able to main personal and collective leadership and management. Those findings lead to the fact that Usrah Mahallah is not only a developing product of Islamisation in IIUM and a platform to develop students’ social, spiritual and intellectual values and skills, but also a principle of good governance in Islam.